Opportunities and Challenges for Islamic Microfinance Institutions in Aceh - Khairil Umuri; Muftahuddin Muftahuddin; Eka Nurlina; Nurma Sari; Junia Farma (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This article examines the challenges and opportunities for Islamic Microfinance Institutions (LKMS) in supporting the strengthening of the Islamic financial system in Aceh following the implementation of Qanun No. 11 of 2018 concerning Islamic Financial Institutions. This study employs a qualitative approach, incorporating in-depth interviews, observations, and secondary data analysis of LKMS financial reports and institutional documents. The research findings indicate that regulatory support and the socio-religious context in Aceh create strategic opportunities for LKMS through a captive market, community preference for halal transactions, and the need for financing in the real sector, especially agriculture, fisheries, and MSMEs. However, the research also reveals significant challenges, including limited human resource capacity, weak capital, low Islamic financial literacy, and the continued dominance of loan shark practices at the community level. Furthermore, government programs that have not been integrated with the LKMS ecosystem add to the complexity of improving the competitiveness of these institutions. This study concludes that the success of LKMS in Aceh cannot rely solely on the existence of regulations, but requires strategies for institutional strengthening, product diversification, digitalisation of services, and increased Islamic financial literacy. The implications of this research emphasise the need for regional government policy support and collaboration with Baitul Mal and socio-religious institutions to create an inclusive and sustainable Islamic financial ecosystem.